Do Hedge Funds Deliver Alpha? A Bayesian and Bootstrap Analysis - KOSOWSKI, Robert (Institutional Knowledge at Singapore Management University, 2007)
Using a robust bootstrap procedure, we find that top hedge fund performance cannot be explained by luck, and that hedge fund performance persists at annual horizons. Moreover, we show that Bayesian measures, which help overcome the short-sample problem inherent in hedge fund returns, lead to superior performance predictability. Relative to sorting on OLS alphas, sorting on Bayesian alphas yields a 5.5 percent per year increase in the alpha of the spread between the top and bottom hedge fund deciles. Our results are robust, and relevant to investors, as they are neither confined to small funds, nor driven by incubation bias, backfill bias or serial correlation.